Planar Chiral Sulfur Compound Derived from [2.2]Paracyclophane: Synthesis and Applications - Le Coz, Arthur; Lhuillier, Warren; Lemouchi, Cyprien; Reboul, Vincent; Perrio, Stéphane (Synthesis, 2025)
Over the past decade, planar chiral sulfur-containing [2.2]paracyclophanes have attracted increasing attention. This review offers a comprehensive overview of the strategies developed to access these appealing derivatives, along with their diverse applications in fields ranging from catalysis to materials science. The discussion is organized according to the type and position of the sulfur functional group within the [2.2]paracyclophane framework.
Keywords: Cyclophanes; Sulfur; Chirality; Stereoselective synthesis; Thiols; Sulfoxides; Thiophenes; Sulfides